PERUBAHAN SIFAT FISIK BUAH TOMAT SETELAH PROSES TRANSPORTASI - Ida Ayu Widhiantari; Sandra Sandra; Gunomo Djoyowasito (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2019)
During the activities of transportation of tomatoes can be damaged due to the vibration frequency of transport machinery and also the transport time. The presence of vibration during the transportation process of tomato fruit can affect change in texture of tomatoes. Optimization is used in this study in order to obtain optimum quality of tomato fruits after simulation transport. Optimization by using Response Surface Methodology (RSM) methods Central Composite Design (CCD) with two independent variables are the vibration frequencies (3 Hz, 6Hz, and 9Hz) and the duration of vibration (90, 120, and 150 minutes) as well as the texture of tomatoes as a response. The optimum conditions obtained in the vibration frequency of 2,32 Hz and transport simulation time 133,42 minutes with optimum texture value of tomatoes is 0,147768 with a value of desirability that 0,928.